Oral manifestations, biochemical, and IL-6 analysis of saliva in major depressive disorder patients under treatment - Fawzi, Omar F; Al-Aswad, Fawaz D (Journal of Baghdad College of Dentistry, 2013)
Background: Major depressive disorder (MDD) is mental disorder characterized by an all-encompassing low mood accompanied by low self-esteem, and by loss of interest or pleasure in normally enjoyable activities. The aims of the study: were to determine the prevalence of oral manifestation among patients with major depressive disorder receiving antidepressant drugs, and detect alkaline phosphatase (ALP), Total Salivary proteins (TSP), and Interleukin-6 (IL-6) in relation to MDD patients under treatment and to compare with healthy controls. Materials and method: (50) MDD patients; between the ages of 20 years and 60 years.The depression patients are divided into (25) patients under treatment with fluoxetine (Prozac), and (25) patients under treatment with imipramine (Tofranil).The depression patients are diagnosed according to Hamilton depression scale used in the department of psychiatry in Al-Yarmouk Teaching Hospital by a psychiatric specialist. Results: The most frequent oral manifestations in the patients with MDD, in this study were burning mouth syndrome (72%), and dry mouth (70%), while metallic taste (48%) was fairly frequent, males more effected than females.Burning mouth syndrome, and metallic taste were more frequent in patients with Prozac treatment, while dry mouth was more frequent in patients with Tofranil treatment. increased levels of IL-6, TSP, and ALP in MDD patients receiving treatment as compared to healthy control Conclusion: frequent oral examination of patients with MDD is mandatory, and these patients should be a major concern in dental practice.